Thirteen week toxicity study of dietary l‐tryptophan in rats with a recovery period of 5 weeks. Issue 4 (16th November 2017) - Shibui, Yusuke; Matsumoto, Hideki; Masuzawa, Yoko; Ohishi, Takumi; Fukuwatari, Tsutomu; Shibata, Katsumi; Sakai, Ryosei
Abstract: Althoughl ‐tryptophan is nutritionally important and widely used in medical applications, toxicity data for its oral administration are limited. The purpose of this study was to evaluate the potential toxicity of an experimental diet containing addedl ‐tryptophan at doses of 0 (basal diet), 1.25%, 2.5% and 5.0% when administered to Sprague–Dawley rats for 13 weeks. There were no toxicological changes in clinical signs, ophthalmology, urinalysis, hematology, necropsy, organ weight and histopathology between control rats and those fed additionall ‐tryptophan. Body weight gain and food consumption significantly decreased throughout the administration period in males in the 2.5% group and in both sexes in the 5.0% group. At the end of the dosing period, decreases in water intake in males in the 5.0% group and in serum glucose in females in the 5.0% group were observed. The changes described above were considered toxicologically significant; however, they were not observed after a 5 week recovery period, suggesting reversibility. Consequently, the no‐observed‐adverse‐effect level ofl ‐tryptophan in the present study was 1.25% for males and 2.5% for females (mean intake ofl ‐tryptophan: 779 mg kg –1 body weight day –1 [males] and 1765 mg kg –1 body weight day –1 [females]). As the basal diet used in this study contained 0.27% of proteinaceousl ‐tryptophan, the no‐observed‐adverse‐effect level of overalll ‐tryptophan was 1.52% for males and 2.77% for females (mean intake of overalll ‐tryptophan: 948 mg kg –1 body weight day –1 (males) and 1956 mg kg –1 body weight day –1 (females)). We conclude thatl ‐tryptophan has a low toxicity profile in terms of human use. Abstract : We performed a study in rats to determine the oral toxicity ofl ‐tryptophan. Adding 5.0%l ‐tryptophan to standard rodent chow produced no overt toxicological changes over a 13 week period. Body weight gain and food consumption significantly decreased throughout the experiment, but these changes were reversible. The total no‐observed‐adverse‐effect level ofl ‐tryptophan was 948 mg kg –1 body weight day –1 for males and 1956 mg kg –1 body weight day –1 for females. We conclude thatl ‐tryptophan has a low toxicity profile in terms of human use.